Photosynthetic acclimation to warming and elevated CO2 in two Antarctic vascular plant species - Bui, Vi NT (Scholarship@Western, 2016)
Climate change can affect the performance of the only two vascular plant species found in Antarctica, Deschampsia antarctica and Colobanthus quitensis. I investigated the response of these two species to warming and elevated CO2 in terms of photosynthesis and leaf anatomy. While photosynthesis increased directly with rising temperature and CO2, it showed no acclimation to changes in growth temperature, and a small degree of acclimation to growth under elevated CO2. Likewise, leaf anatomy displayed little plasticity in response to changes in the growth environment, although D. antarctica’s stomatal groove structure was modified under warming, likely to reduce water loss. Biomass accumulation in both species increased at elevated growth CO2; however, warming suppressed growth in the warmest treatments in D. antarctica, and under all warming treatments in C. quitensis. My results proposed mechanisms for past trends of expanding population in both species and predictions of their performance in future climates.